The α7 Nicotinic Acetylcholine Receptor Agonist GTS-21 Improves Bacterial Clearance via Regulation of Monocyte Recruitment and Activity in Polymicrobial Septic Peritonitis - Hu, Jian-nan; Liu, Ying; Liu, Shu-chang; Zhang, Teng; Chen, Gui-bing; Zhao, Jie; Ma, Tao (Frontiers in Immunology, 2022)
Cholinergic anti-inflammatory pathway has been identified as an effective pathway to modify inflammatory responses, but the influence of cholinergic activation during polymicrobial sepsis has not been well defined. Here, we verified that delayed administration with a selective α7nAChR agonist GTS-21 enables a more efficient elimination of the offending pathogens, diminished inflammatory response and organ injury, and improved survival rates in the polymicrobial septic peritonitis model. And we illustrated that the improved bacterial clearance upon GTS-21 stimulation was accompanied by enhanced recruitment of monocytes into the peritoneal cavity and simultaneously increased phagocytic activity and iNOS expression of these recruited monocytes. Mechanically, splenectomy prior to administration of GTS-21 attenuated the recruitment of monocytes into the peritoneal cavity and abolished the protective benefits of GTS-21 treatment. Meanwhile, GTS-21 administration accelerates the deployment of splenic monocytes during septic peritonitis. Collectively, these data suggested that appropriate selective pharmacological α7nAChR activation promotes monocytes trafficking in a spleen-dependent manner and upregulates the antibacterial activity of recruited monocytes during septic peritonitis, which may be utilized as a promising therapeutic modality for patients suffering from septic peritonitis.